2020
DOI: 10.1029/2019gb006431
|View full text |Cite
|
Sign up to set email alerts
|

Global Model for Depth‐Dependent Carbonyl Photochemical Production Rates in Seawater

Abstract: A photochemical model was used to quantify the global contribution of carbonyl photoproduction in the photodegradation of marine dissolved organic carbon (DOC). As model input, wavelength-and temperature-dependent apparent quantum yields (AQYs) for the photochemical production of carbonyl compounds were determined in seawater collected from the Northwest Atlantic Ocean. These AQY data and published AQY data from the North Pacific were used with remotely sensed seawater optical properties and solar irradiance d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 78 publications
(149 reference statements)
3
16
0
Order By: Relevance
“…The photon exposure in our sunlight-exposure experiments ranged between 161−581 μmol quanta cm −2 , with all except one sample exposed to less than ∼400 μmol quanta cm −2 (Table S1). We have previously shown for carbonyl compounds 46 that photobleaching was only an issue for extended photon exposures when the quantum yields for carbonyl photoproduction decreased (i.e., reciprocity was no longer obeyed). The main uncertainties in our results, and indeed that for anyone who studies photoprocesses in natural waters, are the unknown photobleaching history of samples used in the photochemical experiments and whether CDOM absorption can be used as a proxy to follow/predict the rate of a photochemical reaction in seawater.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The photon exposure in our sunlight-exposure experiments ranged between 161−581 μmol quanta cm −2 , with all except one sample exposed to less than ∼400 μmol quanta cm −2 (Table S1). We have previously shown for carbonyl compounds 46 that photobleaching was only an issue for extended photon exposures when the quantum yields for carbonyl photoproduction decreased (i.e., reciprocity was no longer obeyed). The main uncertainties in our results, and indeed that for anyone who studies photoprocesses in natural waters, are the unknown photobleaching history of samples used in the photochemical experiments and whether CDOM absorption can be used as a proxy to follow/predict the rate of a photochemical reaction in seawater.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Using carbon monoxide as an example, they estimated that surface ocean marine carbon monoxide fluxes amounted to 41 Tg C yr −1 , in line with previous estimates of 30 to 84 Tg C yr −1 . 57,58 More recently, this approach was used with temperature-dependent AQY spectra for acetaldehyde and glyoxal to estimate their annual surface ocean production, 59 and it was found that photoproduction of carbonyl carbon (i.e., glyoxal, methylglyoxal, formaldehyde, acetaldehyde) amounts to 110 Tg C yr −1 . Since these LMW compounds (and CO) are known biological substrates 60 or lost to the atmosphere, their production should also be considered a sink for marine DOM.…”
Section: ■ Perspectivementioning
confidence: 99%
“…However, their contribution to the atmospheric glyoxal budget is poorly constrained. For instance, acetaldehyde is largely produced in seawater (Zhu and Kieber, 2020) and a net flux to the atmosphere is expected (Zhu and Kieber, 2019). Estimates of the global oceanic source of acetaldehyde range from 34 to 57 Tg yr −1 (Millet et al, 2010;Wang et al, 2019).…”
Section: Comparison Of Glyoxal Vcds Between Airborne and Tropomi Obse...mentioning
confidence: 99%